2020
DOI: 10.1515/dmdi-2020-0103
|View full text |Cite
|
Sign up to set email alerts
|

Five genetic polymorphisms of cytochrome P450 enzymes in the Czech non-Roma and Czech Roma population samples

Abstract: AbstractObjectivesCytochromes P450 play a role in human drugs metabolic pathways and their genes are among the most variable in humans. The aim of this study was to analyze genotype frequencies of five common polymorphisms of cytochromes P450 in Roma/Gypsy and Czech (non-Roma) population samples with Czech origin. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The prevalence of the *4 allele in the Medjimurje Roma group is lower than in the European population but still higher than in other world populations. Our results are in concordance with those for Hungarian Roma, Czech Roma, and South Asians [ 64 , 65 ]. CYP2D6*4 creates a deficient protein [ 66 ] and contributes to most of the poor metabolizers observed in European populations.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of the *4 allele in the Medjimurje Roma group is lower than in the European population but still higher than in other world populations. Our results are in concordance with those for Hungarian Roma, Czech Roma, and South Asians [ 64 , 65 ]. CYP2D6*4 creates a deficient protein [ 66 ] and contributes to most of the poor metabolizers observed in European populations.…”
Section: Discussionsupporting
confidence: 92%
“…Dlouhá et al reported no significant difference in the genotype/allelic frequencies of CYP2D6 (rs1065852) in Roma/Gypsy and Czech (non-Roma) populations. 25 However, Zhang et al observed the frequency of CYP2D6 rs1065852 in the Lisu population different from the other populations. 26 In our study, rs1065852-A frequency was the highest in the South East Asian populations.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in Roma, allelic differences in lactate dehydrogenase (Hubácek et al., 2017b), drug metabolism enzymes (Tomas et al., 2017, Dlouhá et al, in press), or osteoprotegerin (Mydlárová Blaščáková et al., 2017) polymorphisms clearly underlie genetic differences that could have important clinical (optimal treatment or dietary recommendations) or live expectancy consequences.…”
Section: Discussionmentioning
confidence: 99%